Role of trivalent Bi/Tm partial substitution on active operable slip systems in Bi-2212 crystal structure - Erdem, Ümit; Zalaoğlu, Yusuf; Ülgen, Asaf Tolga; Turğay, Tahsin; Yıldırım, Gürcan (ELSEVIER LTD, 2021)
This study delves into three main subjects: (I) A strong definition on the variation of fundamental key mechanical design performance and general mechanical characteristic features founded on the formation of active operable slip systems and elimination of structural problems in the Tm substituted Bi-site Bi2.1-xTmxSr2.0Ca1.1Cu2.0Oy (0.00 ≤ x ≤ 0.30) ceramic materials; (II) Preference of propagation of cracks and dislocation movements (III) An examination of differentiation in the load-independent microhardness parameters in the saturation limit regions with the Bi/Tm partial replacement. It is found that all the mechanical performance (mechanical strength, stiffness, durability and resistant towards to the failure by fatigue) properties considerably improve with the increment in the Bi/Tm substitution level up to x = 0.07 due to the augmentation in the new active operable slip systems and crystallinity quality of Bi2.1Sr2.0Ca1.1Cu2.0Oy (Bi-2212) system. Accordingly, in case of the optimum Bi/Tm substitution the propagation of dislocation and crack movements is more and more easily controlled in the Bi-2212 ceramic system. However, the excess Tm concentrations in the ceramic system make the stress-induced phase transformation remarkably activate as a consequence of the degradation in the crack orientation and geometry. Hence, any deformation at even lower applied test loads is much more permanent and non-recoverable due to the enhancement of unconstrained dislocation motions and especially entanglement of cracks and dislocations. This fact is also confirmed from the reduction of typical indentation size effect (ISE) behavior in the event of excess Tm concentration. To conclude, the optimum Bi/Tm partial replacement in the Bi-2212 crystal structure is successful to improve the economic lives of Bi-2212 inorganic ceramics in the new, novel, innovative, feasible and potential design areas for the universe economy.
Keywords: Bi-2212 ceramic system; Bi/Tm partial replacement; Propagation; Slip systems; Transgranular regions; Vickers hardness